Fast software encryption : 22nd International Workshop, FSE 2015, Istanbul, Turkey, March 8-11, 2015, Revised selected papers /: 22nd International Workshop, FSE 2015, Istanbul, Turkey, March 8-11, 2015, Revised selected papers. (2015) - Unknown
No abstract available